Desymmetrization of Perylenediimide Bay Regions Using Selective Suzuki–Miyaura Reactions from Dinitro Substituted Derivatives. Issue 68 (6th October 2020) - Hruzd, Mariia; Rocard, Lou; Goujon, Antoine; Allain, Magali; Cauchy, Thomas; Hudhomme, Piétrick
Abstract: Bay decoration of perylenediimide (PDI) is an attractive approach for tuning the optoelectronic properties of the dye as well as breaking backbone planarity, which provides the possibility of preventing the undesired formation of aggregates. This is usually performed through successive bis‐bromination of PDI and pallado‐catalyzed cross‐coupling, which leads to symmetric triads. We now describe an efficient synthetic strategy for desymmetrization of the accepting PDI core by starting from its bis‐nitration. To this end, Suzuki–Miyaura Couplings (SMC) were carried out on a mixture of 1, 6‐ and 1, 7‐dinitroPDI regioisomers to add triphenylamine donating moieties and obtain donor–acceptor–donor triads. Investigation of the reactivity of dinitro PDI derivatives toward SMC has allowed us to access unprecedented asymmetric π‐conjugated PDI‐centered triads. These 1, 6‐ and 1, 7‐PDI based triads, prepared as regioisomeric mixtures, were successfully separated and their spectroscopic, crystallographic and optoelectronic differences are reported. Abstract : The bay decoration of perylenediimide (PDI) through C−C bond formation was achieved by Suzuki–Miyaura couplings using a dinitro precursor. The unique reactivity of this electrophilic partner in comparison with its brominated analogue is highlighted and it allows for the first easy asymmetric π‐decoration of the PDI core, opening new horizons for this new class of functional materials.